Hidrólise controlada de proteínas do soro de queijo usando carboxipeptidase A e alcalase® imobilizadas multipontualmente em agarose - Tardioli, Paulo Waldir (Universidade Federal de São Carlos, 2003)
High value food protein hydrolysates can be obtained by sequential hydrolysis of proteins with trypsin, chymotrypsin, carboxypeptidase A (CPA) and Alcalase® (commercial preparation of subtilisin). For the process to be economically feasible, immobilized and stabilized enzymes should be used, and the kinetics of the reactions with this kind of biocatalyst must be known. To contribute to the development of such a process, this work focused on preparing stable CPA and Alcalase® derivatives, and on studying the kinetics of hydrolysis of polypeptides. These polypeptides were produced after the sequential hydrolysis of cheese whey proteins with trypsin and chymotrypsin. Cross-linked agarose beads (6% w/w for CPA, and 10% w/w for Alcalase®) were used as immobilization support, and different methods of activation and immobilization conditions were studied. A highly activated glyoxyl-agarose support (75 and 210 µeqv of aldehyde groups per milliliter of support, respectively for CPA and Alcalase®), 25oC, pH 10.05, and longer contact time (48 hours for CPA and 96 hours for Alcalase®), provided the best derivatives. CPA-glyoxyl agarose-6% and Alcalase®-glyoxyl agarose-10% derivatives were ca. 213- and 515-fold more stable than the soluble enzymes. These stabilized derivatives retained 42% (for CPA-glyoxyl agarose- 6%) and 54% (for Alcalase®-glyoxyl agarose-10%) of the immobilized activity, assessed with small substrates (hippuryl-L-Phe for CPA, and Boc-Ala-ONp for Alcalase®) and large substrates (Phe carboxy-terminal polypeptides for CPA, and casein for Alcalase®). These results showed that all activity losses were caused by the distortion of the immobilized enzyme molecule, due to the enzyme-support multi-interaction. Derivatives prepared using glutaraldehyde-agarose presented spatial hindrances when hydrolysis of macromolecular substrates was taking place. The amino acid analysis of acid hydrolysates of the soluble and immobilized enzymes (for the more stable derivatives) showed that ca. 30 and 40%, for CPA and Alcalase®, of the lysine residues were linked to the support, suggesting that there is intense multi-point interactions between enzyme and support, through covalent linkages. The temperatures for maximum hydrolysis rates, using respectively stabilized CPA and Alcalase® derivatives, were 20oC and 10oC higher than the ones obtained using soluble enzymes. The most stable CPA-glyoxyl derivative could efficiently be used for polypeptides (cheese whey proteins hydrolyzed with trypsin and chymotrypsin) hydrolysis at high temperatures (e.g., 60oC), releasing ca. 2-fold more aromatic amino acids (Tyr, Phe and Trp) than the soluble enzyme, under the same operational conditions. The casein degree of hydrolysis, at 80oC, obtained using the most stable Alcalase®-glyoxyl derivative, was 2-fold higher than the one obtained with the soluble enzyme. Hence, the produced derivatives allow the design of a continuous process for the production of protein hydrolysates, which are composed of small peptides and have a low concentration of aromatic amino acids. This process can use higher temperature, avoiding microbial growth in the reaction medium. The C-terminal residues hydrolysis at 45oC (pH 7.0), catalyzed by CPA-glyoxyl, could be adequately represented by Michaelis-Menten kinetics, with substrate and product inhibition. The kinetic model was expressed in terms of C-terminal peptide bonds that can be hydrolyzed by CPA, regardless of the amino acid released. The concentration of each released amino acid as a function of the time of reaction could be well fitted by empirical models (hyperbolic or exponential decay). Hence, from the kinetics of total hydrolysis, it is possible to estimate the concentration of each amino acid as function of time. The hydrolysis catalyzed by the highly-loaded CPA-glyoxyl agarose-6% derivative was not limited by intra-particle diffusion resistance. The hydrolysis of peptides (long-time batch) at 50oC (pH 9.5), catalyzed by Alcalase®-glyoxyl agarose-10% derivative, could be adequately represented by Michaelis-Menten kinetics with product inhibition, and the kinetic parameters Vmax, KM e KI were correlated against the substrate initial degree of hydrolysis (total degree of hydrolysis obtained by previous action of trypsin and chymotrypsin on cheese whey proteins). Long-time batch hydrolyses, catalyzed by highly-loaded Alcalase-glyoxyl agarose-10% derivative, presented diffusion effects, with effectiveness coefficient, ηI, of ca. 0.5.
Keywords: Tecnologia de enzimas; Alcalase®; Carboxipeptidase A; Glioxil - agarose; Cinética de hidrólise de polipeptidios; ENGENHARIAS::ENGENHARIA QUIMICA